Stigma and stratification limiting the math course progression of adolescents labeled with a learning disability. (April 2016) - Shifrer, Dara
Abstract: Learning disability (LD) designations may produce stigma by masking the real causes of learning differences, altering perceptions, and legitimizing stratification. This study uses data on adolescents and their teachers from The Education Longitudinal Study of 2002 to show the negative effect of LD designations on adolescents' math course attainment is partially mediated by disparities in adolescents' earlier math course placements, and teachers' more negative attributions and expectations. Results indicate addressing low achievement through LD designations may reproduce disadvantage through stigma and stratification. Highlights: Teachers' expectations are higher for low achievers with no disability designation. Teachers less often attribute undesignated low achievers' performance to disability. Designated adolescents' course levels are inconsistent with previous performance. Stigma and stratification contribute to designated adolescents' poorer outcomes.